(untitled) (Agricultural Engineering, 2016)
The object of the research is a technological process and technical means of cutting woody shrubs at melioration objects. The subject of the research consists of regularities and methods of execution of the process of cutting woody shrubs at melioration objects by a multirotor mower with trapezoidal knives. The aim of the research is to increase efficiency of cutting shrubs at melioration objects by applying a multi-rotor mower with trapezoidal knives. We have obtained analy tical dependences in order to determine the angle of diversion of a knife from the radial position during contact with the stem, and to calculate the reaction in the joint “knife-fixing bolt” depending on the parameters of a knife and rotor, and the distance from the centre of the knife fixing bolt to the point of contact of a knife and stem, which provides minimal impact load on the knife fixing bolt during cutting woody shrubs. We have also developed a mathematical model of the process of cutting shrubs by a multi-rotor mover with trapezoidal knives, and methods of determination of the main parameters and regimes of work of the mower cutting apparatus for cutting shrubs at melioration objects, which contain a monogram, based on the use of theoretical-experimental dependences.